Management of Medicines Wastage, Returned Medicines and Safe Disposal in Malaysian Community Pharmacies: A Qualitative Study - Chong, Kah Mun; Rajiah, Kingston; Chong, David; Maharajan, Mari Kannan (Frontiers in Medicine, 2022)
Introduction In supplying medicines to patients and consumers waste can occur in prescribing, dispensing, and leftover stages. Pharmacists in community pharmacies play a crucial role in dispensing and should share information on appropriate medicines disposal with consumers. This qualitative study explored how Malaysian community pharmacists manage medication wastage, returned medicines, and medicines disposal by eliciting their opinions on medicines wastage, the challenges faced, and feasibility of medicine return and safe medicine disposal in the setting of Malaysian community pharmacy. Methods Telephonic interviews were conducted using a pre-validated interview guide among community pharmacists. Purposive sampling was used to ensure heterogeneity of participants in terms of gender, age, and position in the pharmacy. The interview was conducted until a point where no new information was obtained. Interview data were thematically analyzed. Results The analysis identified nine themes organized into four domains. The results revealed that pharmacists have positive perceptions of the safe disposal of medicines. Pharmacists mentioned that medicine returns to service in community pharmacies are not common due to a lack of facilities in the management of unwanted, expired, and returned medicines. As such pharmacists have suggested a few ways to minimize medicinal wastage. Conclusions Respondents aimed to minimize medicines wastage (unused medicines) in order to minimize loss of revenue. Respondents did not usually accept returned medicines due to the operational costs of safe disposal. Disposal of unused medicines was undertaken by centralizing the stocks at an organization facility before being disposed of by outsourced waste management companies.